The value of education and work in the representatives of gymnasts' opinion - Perzynska-Biskup, A.; Sawczyn, S. (Baltic Journal of Health and Physical Activity, 2010)
Background: Sports professional activity has been an unusually absorbing domain of human life. This is particularly noticeable in so-called sports of early specialization, including gymnastics. The specialization in gymnastics occurs at the moment of girls' acquisition of knowledge and preparation for future professional careers. Therefore, the authors decided to look further into the process of combining school and sports duties and to reveal possible conflicts.